Health Information Media Literacy on Instagram Sehat Surabayaku - Excell Pradana; Edelweis Putri Prima (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This study aims to examine the level of media literacy and public response to health information provided by the Instagram account @sehatsurabayaku during the period May to June 2023. Media literacy is a crucial aspect in understanding, assessing and interpreting health information circulating on social media. This study uses the content analysis method to identify the type, source, and accuracy of health information published by the Instagram account @sehatsurabayaku. In addition, a survey was conducted to collect data on people's understanding and perception of health information received from these accounts. Survey respondents were randomly selected from followers of the Instagram account @sehatsurabayaku who were active during the study period. The results of this study are expected to provide an understanding of the extent to which people's media literacy processes health information from certain social media, especially the Instagram account @sehatsurabayaku. The findings of this study can provide insight for stakeholders in the health and social media fields in developing a more effective and responsible communication strategy